Analisis Strategi Bersaing Usaha Makanan Khas Daerah Pariaman Ditinjau dalam Perspektif Bisnis Syariah : (Studi Kasus: Ulakan Tapakis) - Sutia Putri; Novera Martilova (Universitas 17 Agustus 1945 Semarang, 2024)
This research has the aim of being able to find out and analyze the competitive strategies carried out in regional specialty food businesses amidst many competitors and to find out how the sharia business perspective in the competitive strategy of regional specialty food businesses in Ulakan Tapakis. This research uses qualitative descriptive research methods. This type of qualitative descriptive research is research where the aim is to provide descriptions of facts and characteristics related to the phenomenon being studied. This qualitative research aims to produce data in the form of verbal words and how the business behavior is being observed. This research was conducted through direct observation and interviews with regional specialty food traders in Ulakan Tapakis and market managers in Ulakan Tapakis. The results of this research are business competitive strategies carried out by regional specialty food traders in Ulakan Tapakis. And a review of sharia business in the business competitive strategy carried out by each regional specialty food business trader in sharia business, whether it is in accordance with sharia business in the implementation of its business strategy in order to gain an advantage in competing in regional specialty food businesses with strategies implemented by traders such as: strategy promotions, pricing strategies, service strategies, strategies for improving taste quality, and marketing strategies implemented by regional specialty food business traders related to the business strategies they carry out from a sharia business perspective.